Swamy's compilation of F.R. & S. R.- Part IV dearness allowance dearness relief and house rent allowance - Muthuswamy; Brinda; Sanjeev (Chennai Swamy Publishers, 2024)
Shri Muthuswamy has already published several useful compilations of Government rules and regulations. Government rules and orders tend to accumulate and are subject to many changes in keeping with the dynamics of modern Government and the changing pattern of its relations with its employees. Official and unofficial literature on Government rules and regulations and a reliable book for reference
Keywords: Govt. House Rent Allowance; Dearness Allowance